EXAMINATION OF THE LOCAL MECHANICAL BEHAVIOR AFTER WELDING - Bozkurt, Fatih; Schmidová, Eva (Žilinská univerzita, 2016)
High strength steels used for rail vehicles chassis create advantages such as reduced weight, reduction of fuel consumption and increased payload. This motivation to convert the rail vehicles is currently substantially restricted due to effect of welding. The complex study of structural and mechanical changes caused by particular welding technology is necessary for successful adaptation of the improved steels grades. Domex 700MC, a thermo-mechanically hot rolled cold forming steel, characterized by a low carbon content and small additions of microalloying elements was tested in this study. The steel grade of S355 was examined as comparative commonly used steel.
Hodnocení lokálních mechanických parametrů po svařování
Keywords: dynamic yield strength; heat affected zone; local mechanical parameters; dynamická mez kluzu; tepelně ovlivněná oblast; lokální mechanické vlastnosti